Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
The Selected Issues paper describes the nexus between household wealth, saving, and consumption, and provides estimates for the medium-term path of household saving and consumption. The paper also discusses to what extent the credit market frictions are holding back Ireland's economic recovery. Under current macroeconomic assumptions, the savings rate is expected to decline. Households have rapidly accumulated debt during boom times, and incomes and asset values have declined severely during the crisis. The Executive Board welcomes the country's efforts toward economic recovery.